EXPLORING TEACHERS’ STRATEGIES IN TEFL - Tambunan, Rofriyanti Veronika; Masagus Firdaus; Hanni Yukamana (Esteem Journal of English Education Study Programme, 2025)
This research explores the teachers’ teaching strategies in teaching English as a foreign language at SMP Bethesda Palembang. Kayi’s theory has fifteen strategies that can be applied by English teachers to teach speaking in the teaching and learning process. Several teaching methods include discussion, role-play, simulation, information gap, brainstorming, story-telling, interview, story completion, reporting, card games, picture narration, picture description, and spotting the differences. A qualitative descriptive method was utilized for this research, and two teachers as samples. To gather data, the researcher used questionnaires, interviews, and documentation as instruments in this research. The results of this research show that Teacher 1 employed strategies such as conversation, speeches, interviews, and discussions. In contrast, Teacher 2 used presentations, reporting, project-based learning, games, interviews, and story retelling. Teachers use those strategies because the strategy makes the students participate in teaching and learning activities. Overall, the teachers implemented a variety of strategies to teach speaking skills.